Inhibitory Effects and Mechanisms of Luteolin on Proliferation and Migration of Vascular Smooth Muscle Cells - Jiang, Dehua (MDPI, 2013)
Atherosclerosis (AS) is a complicated progress, involving many types of cells. Although the exact mechanisms of progression of atherosclerosis are uncertain, the balance of vascular smooth muscle cells (VSMCs) proliferation and apoptosis appears to play a pivotal role in the pathogenesis and progression of atherosclerosis, and much discussion has been undertaken to elucidate the detailed mechanisms, relevant gene expression and transduction pathways. Drug treatment has focused on ameliorating atherosclerosis. Some researchers have indicated that inhibiting VSMCs proliferation is involved in attenuating atherosclerosis. Luteolin is a kind of flavonoids naturally occurring in many plants and possesses beneficial effects on cardiovascular diseases. Luteolin can reduce VSMCs’ proliferation and migration and this reduction is stimulated by several factors. The aim of this review is to summarize the existing inhibitory effects and mechanisms of luteolin on proliferation and migration of VSMCs, and consider whether luteolin may be a potential candidate for preventing and treating atherosclerosis.